ABOUT THE TERM OF PERSUASION (Scientific journal of the Fergana State University, 2024)
AbstractThis article describes the meaning of the term persuasiveness, which was adopted from the science of psychology into linguistics. The concepts of “persuasion” and “persuasion,” which were originally defined in the psychological literature by the term persuasion, were brought into linguistics under the name of persuasiveness, retaining their essence. In linguistics, this concept, which is assessed as a method of influence through speech, is called persuasiveness in Russian linguistics, and persuasion in English and German linguistics. Despite the fact that in Uzbek linguistics there are a number of scientific views related to the influence of speech, the term expressing the content of instilling trust in the addressee with the help of speech and thereby changing his thoughts and views does not appear. In linguistics, the word persuasion - from the Latin persuasio - meaning to convince, convince - is used to determine the level of reliability of information based on the criteria of “reliable” or “unreliable”. This term was first introduced into scientific circulation in the field of stylistics in linguistics. Later, persuasiveness began to be studied in harmony with issues of text linguistics, psycholinguistics, cognitive linguistics, and speech effects. The article is addressed to representatives of Russian linguistics, as well as world linguistics. When covering the topic, methods of observation, comparative analysis, classification and generalization were actively used. As a result of the study, theories about the term persuasiveness are analyzed and tools that give persuasive meaning to discourse are identified.